Effects of the Prostaglandin E1 Analog Limaprost on Mechanical Allodynia Caused by Chemotherapeutic Agents in Mice - Punam Gauchan; Tsugunobu Andoh; Atsushi Kato; Atsushi Sasaki; Yasushi Kuraishi (Elsevier, 2009)
This study examined in mice whether limaprost, a prostaglandin E1 analog, would relieve allodynia induced by chemotherapeutic agents. Single intraperitoneal injections of paclitaxel, oxaliplatin, and vincristine sulfate induced and gradually increased mechanical allodynia. Repeated administration of limaprost alfadex inhibited the late, but not early, phase of mechanical allodynia induced by paclitaxel and oxaliplatin, but not vincristine. Paclitaxel and oxaliplatin, but not vincristine, gradually decreased peripheral blood flow, which was prevented by limaprost. These results suggest that limaprost is effective against mechanical allodynia induced by paclitaxel and oxaliplatin, which may be due to inhibition of the decrease in peripheral blood flow. Keywords:: limaprost, chemotherapeutic agent-induced mechanical allodynia, peripheral blood flow